(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Assessing several factors related to the prevalence of overweight and obesity among students at Tran Hung Dao Primary School, Thai Binh City, in 2025. Method: From August 2024 to August 2025, a cross-sectional descriptive study was conducted on 1123 students from grades 1 to 5 currently studying at the school. Results: Factors related to overweight and obesity in children include: boys are at higher risk than girls; children have a family history of overweight or obesity; children have a birth weight ≥ 3.5 kg; children have a habit of eating quickly; children have their last meal after 8 PM; children have a habit of eating fried foods; children have a habit of eating fast food/sweets; children do not exercise regularly; children watch television for more than 2 hours/day. Conclusion: The results suggest that early intervention through improved nutrition, increased physical activity, and reduced sedentary time is necessary to reduce the prevalence of overweight and obesity in this group of children.